Armenians from Moldavia in Transylvania, Hungary and the Larger World. A Case Study - GOROVEI, Ştefan S. (Studia Universitatis Babeș-Bolyai Historia, 2019)
The same family name – Gorovei – was common in the principality of Moldavia (Neamţ county, then Dorohoi and others), from the beginning of the seventeenth century, and in the principality of Transylvania (at Gherla / Armenopolis / Szamosújvár, then also in other locales in Banat and in Hungary), from the beginning of the eighteenth century. Those who carried the name in Moldavia (then Romania) were Orthodox Romanians. Those from Transylvania (then Hungary) – whose name took the form Gorove – were Catholic Armenian (united with the Church in Rome). From among these, the best known are Gorove László (1780–1839) and his son Gorove István (1819–1881, minister in 1867–1871), members of the Hungarian Academy, as well as Gorove Antal (1822–1881), a military man and lawyer. Artur Gorovei (1864–1951) – writer and folklorist, member of the Romanian Academy, and passionate genealogist – initiated research on his family history, trying to find an answer to the question of whether the bearers of the same patronym could, somehow, share a common distant ancestor. Due to the lack of documentary evidence, but also due to how the issue was understood as a whole, he did not reach a firm conclusion, oscillating instead between a hypothetical assertion and an uncertain denial. Continuing this research into family history, the author of the present study also reached the same “enigma” relative to which he initially maintained a reluctant position. He then proposed to address the issue within a wider context with an emphasis on the name (patronym) itself. On the one hand, this led to the formation of a program of researches focused on the bearers of the name Gorovei. On the other hand, a recent discovery has guided the research in a more reliable direction. A document found in the Vienna archives mentions a group of Armenians from Gherla in 1759, including senator Abagarus Gorovei and senator Christophorus Gorovei (the ancestors of the two family branches knighted by Empress Maria Theresia in 1760-1761). These Armenians declare that they belong to those who came to Transylvania from Moldavia (nos aeque e numero illorum Armenorum esse, qui […] e Moldavia in Transylvaniam venerunt). The author believes that this testimony is decisive in establishing an answer to the “enigma”: he advances the hypothesis that the bearers of the name Gorovei from Moldavia and Transylvania (Hungary) are two branches that descend from a common ancestor of Armenian origin. Given the genealogical and chronological correlations between the two branches, this hypothetical common ancestor had to live in Moldavia in the middle of the sixteenth century. This period coincides with the great persecution of the Armenians ordered by the prince Ştefan VI Rareş (1551–1552). In the author’s hypothesis, an Armenian Gorovei accepted to convert, under those circumstances, to Orthodoxy. He would have been the ancestor of the Gorovei whose history unfolded in the principality of Moldavia. At the same time, one of those who resisted the pressures and preserved the faith would be the ancestor of whose who crossed the Carpathians and established in Gherla, either toward the end of the seventeenth century or the beginning of the eighteenth century. The second part of the study (Addenda) is devoted to the clarification of several controversial genealogical connections – the family branch of Gorove Antal and that of Gorove Viktor, both closely interwoven in the history of Transylvania during the nineteenth century. Rezumat: Armeni din Moldova în Transilvania, Ungaria și-n lumea largă. Un studiu de caz. Un același nume de familie – Gorovei – a fost purtat, în principatul Moldovei (ținutul Neamț, apoi Dorohoi și altele), de la începutul secolului XVII, iar de la începutul secolului XVIII în principatul Transilvaniei (la Gherla / Armenopolis / Szamosújvár, apoi și în alte localități, în Banat și în Ungaria). Purtătorii numelui din Moldova (apoi România) erau români ortodocși. Cei din Transilvania (apoi Ungaria) – al căror nume a devenit cunoscut sub forma Gorove – erau armeni catolici (uniți cu Biserica Romei); dintre aceștia, cei mai cunoscuți sunt Gorove László (1780–1839) și fiul său Gorove István (1819–1881, ministru în 1867–1871), membri ai Academiei Maghiare, precum și Gorove Antal (1822–1881), militar și jurist. Artur Gorovei (1864–1951), scriitor și folclorist, membru al Academiei Române, genealogist pasionat, a inițiat cercetări privind istoria familiei sale, în cadrul cărora a încercat să găsească un răspuns și la întrebarea dacă, în aceste condiții, purtătorii aceluiași patronim aveau, cumva, și un îndepărtat strămoș comun. Din cauza insuficienței materialului documentar, dar și prin felul cum a fost văzută problema în ansamblu, el nu a ajuns la o concluzie fermă, oscilând între afirmarea ipotetică și negarea nesigură. Continuând aceste cercetări de istorie familială, autorul prezentului studiu s-a lovit și el de aceeași “enigmă”, față de care a păstrat, inițial, o poziție reticentă, propunând însă abordarea problemei într-un cadru mai larg, în care accentul să fie pus pe numele (patronimul) însuși. Aceasta a dus la configurarea unui program de cercetări privind purtătorii numelui Gorovei. Pe de altă parte, o descoperire recentă a îndrumat cercetările respective pe o cale mai sigură. Un document identificat în arhivele din Viena menționează, la 1759, un grup de armeni din Gherla, între care Abagarus Gorovei senator și Christophorus Gorovei senator (strămoșii celor două ramuri înnobilate de împărăteasa Maria Theresia în 1760-1761); acești armeni declară că ei fac parte dintre aceia care au venit în Transilvania din Moldova (nos aeque e numero illorum Armenorum esse, qui […] e Moldavia in Transylvaniam venerunt). Autorul crede că această mărturie este decisivă în aflarea unui răspuns la respectiva “enigmă”: el avansează ipoteza că purtătorii numelui Gorovei din Moldova și Transilvania (Ungaria) reprezintă două ramuri care descind dintr-un strămoș comun de origine armeană. Date fiind coordonatele genealogice și cronologice ale celor două ramuri, acest ipotetic strămoș comun a trebuit să trăiască în Moldova pe la mijlocul secolului XVI; or, această perioadă coincide cu marea persecuție a armenilor ordonată de principele Ștefan VI Rareș (1551–1552). În ipoteza autorului, un Gorovei armean a acceptat să se convertească, în acele împrejurări, la Ortodoxie; el ar fi strămoșul Goroveilor a căror istorie s-a desfășurat în principatul Moldovei, în timp ce unul dintre cei care au rezistat presiunilor și și-au păstrat confesiunea ar fi strămoșul celor care, la sfârșitul secolului XVII sau la începutul celui următor, au trecut Carpații stabilindu-se la Gherla. Partea a doua a studiului (Addenda) este consacrată clarificării unor conexiuni genealogice controversate – ramura lui Gorove Antal și cea a lui Gorove Viktor, ambele interesând îndeaproape istoria Transilvaniei în secolul XIX. Cuvinte-cheie: istorie familială, genealogie, armeni, Moldova, Transilvania, Gorovei/Gorove, strămoș comun.